2022
DOI: 10.1101/2022.01.06.475187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

scRNA-sequencing reveals subtype-specific transcriptomic perturbations in DRG neurons ofPirt-EGFPfmice in neuropathic pain condition

Abstract: Functionally distinct subtypes/clusters of dorsal root ganglion (DRG) neurons, which differ in soma size and neurochemical properties, may play different roles in nerve regeneration and pain. However, details about transcriptomic changes in different neuronal subtypes under maladaptive neuropathic pain conditions remain unclear. Chronic constriction injury (CCI) of the sciatic nerve represents a well-established model of neuropathic pain that mimics the etiology of clinical conditions. Therefore, we conducted … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The component heterogeneity of somatosensory neurons in the DRG is essential to relay different peripheral inputs to the central nervous system (Abraira and Ginty, 2013;Gatto et al, 2019;Li et al, 2016;Todd, 2010). The heterogeneity in the molecular transcriptomes, neuronal types, and functional properties of DRG neurons in rodents has been well characterized (Hu et al, 2016;Li et al, 2016;Renthal et al, 2020;Usoskin et al, 2015;Wang et al, 2021a;Zhang et al, 2022;Zhou et al, 2022). Recently, emerging evidence has revealed the organization of human DRG somatosensory neurons (Jung et al, 2023;Nguyen et al, 2021;Tavares-Ferreira et al, 2022;Yu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The component heterogeneity of somatosensory neurons in the DRG is essential to relay different peripheral inputs to the central nervous system (Abraira and Ginty, 2013;Gatto et al, 2019;Li et al, 2016;Todd, 2010). The heterogeneity in the molecular transcriptomes, neuronal types, and functional properties of DRG neurons in rodents has been well characterized (Hu et al, 2016;Li et al, 2016;Renthal et al, 2020;Usoskin et al, 2015;Wang et al, 2021a;Zhang et al, 2022;Zhou et al, 2022). Recently, emerging evidence has revealed the organization of human DRG somatosensory neurons (Jung et al, 2023;Nguyen et al, 2021;Tavares-Ferreira et al, 2022;Yu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, we still know little about the interactions between the various neuronal components of the DRG and spinal cord. Wang et al reported that DRG TRPV1 + neuron-spinal ErbB4 + neuron connections are involved in heat sensation and that NRG1-ErbB4 signaling is related to heat hypersensitivity induced by nerve injury (Wang et al, 2022). However, which DRG neuronal types secrete NRG1 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The trans-activation of the uninjured afferents as a result of injury to a subset of neighboring afferents has been observed in several disease settings including post colitis or nerve injury pain (Fukuoka et al, 1998;Traub et al, 1999;Gold, 2000;Gold et al, 2003;Obata et al, 2004;Obata et al, 2006;Qiao and Grider, 2009;Lei and Malykhina, 2012;Tran and Crawford, 2020;Kalpachidou et al, 2022). A recent study using single cell RNAseq of DRG neurons in nerve injury models demonstrates distinct molecular profiles in the injured (Sprr1a + ) and uninjured (Sprr1a -) neurons in the same ganglia (Zhang et al, 2022a). For instance, the injured neurons have reduction of potassium and sodium channels, Calca, Sst and Tac1 expression, while the uninjured neurons have upregulation of Cacna2d1, Tgfb1 and Gal, etc.…”
Section: Inflammation/injury Induces Molecular Changes In Uninjured D...mentioning
confidence: 99%
“…For instance, the injured neurons have reduction of potassium and sodium channels, Calca, Sst and Tac1 expression, while the uninjured neurons have upregulation of Cacna2d1, Tgfb1 and Gal, etc. (Zhang et al, 2022a). The uninjured neurons also contain upregulation of many differentially expressed genes (DEGs) that are related to protein biosynthesis, nerve regeneration and pain (Zhang et al, 2022a).…”
Section: Inflammation/injury Induces Molecular Changes In Uninjured D...mentioning
confidence: 99%
See 1 more Smart Citation